Digital-Based Pop Up Book To Improve Toothbrushing Behavior in Deaf Children - Maulidiah, Tikha Fatikha; Supriyana, Supriyana; Santoso, Bedjo (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2025)
Deaf children are those with limited hearing, which affects the reception of information, including knowledge about dental and oral hygiene. As a result, many deaf children have moderate to poor debris index scores. This is largely due to a lack of awareness about the importance of maintaining dental hygiene. One strategy to address this issue is using “digital-based pop up book media,” which offers engaging and enjoyable education during the learning process. This study aimed to develop and assess the effectiveness of such media in improving toothbrushing behavior and reducing the debris index in deaf children.This research was conducted using a research and development (RD) approach with a quasi-experimental pretest-posttest group design. The sample consisted of 22 deaf children, with 11 in the intervention group (SLBN Semarang) and 11 in the control group (SLBN Ungaran), selected using the Slovin formula. Data were analyzed using the Intraclass Correlation Coefficient, Shapiro-Wilk, Paired t-test, Wilcoxon, and Mann Whitney tests.Results showed significant improvements in the intervention group. Knowledge scores (p = 0.002, Δ = 1.36), attitudes (p = 0.004, Δ = 1.36), skills (p = 0.007, Δ = 2.91), and debris index (p = 0.000, Δ = 1.364) improved more significantly compared to the control group.In conclusion, digital-based pop up book media is a feasible and effective method to enhance toothbrushing behavior and reduce the debris index among deaf children.